Effect of Ramadan Fasting on Peptic Ulcer Disease and Peptic Perforation (Medical Forum Monthly, 2024)
Objective: To compare the frequency of patients presenting with peptic ulcer disease (PUD) and peptic perforation during holy month of Ramadan with those presenting the month after Ramadan (Shawwal) in the Hijrah calendar and to assess the effect of risk factors on PUD and peptic perforation such as smoking, non-steroidal anti-inflammatory drugs usage, a previous history of acid peptic disease and the age groups and gender of patients.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was carried out in Medical and Surgical Units of KTH (Khyber Teaching Hospital) Peshawar from 2012 to 2014..Research Methodology: A total of 213 patients were included in this study presenting during this three years period. Patients were included or excluded according to a pre-set “inclusion or exclusion criteria”.Results: 62%(132) of all the patients presented during the three months of Ramadan as compared to 38%(81) of the patients presented three months after the Ramadan, x2=8.193, P value is 0.004205 and result is significant at p<0.05.Ninety six(46%) patients were smokers, 132(62%) of the patients were in the 20 to 40 year age group and male to female ratio was 5:1.Symptoms associated with peptic ulcer disease found in patients during Ramadan is more than after Ramadan.Conclusions: This study clearly showed the increased frequency of peptic ulcer disease and peptic perforation during the Holy month of Ramadan stresses on the need of precaution especially for smokers, non-steroidal anti-inflammation drugs users and patients with the history of acid peptic disease during this month.